2012
DOI: 10.1074/jbc.m111.325654
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Ligand-binding Site in Cytochrome P450 3A4 Located with Fluorescence Resonance Energy Transfer (FRET)

Abstract: Background: Cytochrome P450 3A4 (CYP3A4) can bind several substrate molecules simultaneously and exhibits cooperativity. Results: Ligand binding in the active site is preceded by functionally important interactions at a distinct peripheral site. Conclusion: The mechanism of cooperativity involves a ligand-induced allosteric transition. Significance: Allosteric mechanism suggested by our results transforms the view of the grounds and significance of CYP3A4 cooperativity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 47 publications
7
92
1
Order By: Relevance
“…Taken together, the results of cross-linking and LRET studies indicate that one of the subunit interfaces is similar to that observed in the CYP3A4 x-ray structure 1W0F, where Cys 239 residues of two subunits are located in close proximity to each other. These findings strengthen our prior inference that the peripheral steroid-binding site in the vicinity of the FЈ and GЈ helices of two interacting CYP3A4 molecules observed in the x-ray structure 1W0F is physiologically relevant (23,61). The interactions at the second type of the intersubunit interface are also likely to bring some cysteine residues other than Cys 239 of two CYP3A4 subunits into close proximity to each other.…”
Section: Discussionsupporting
confidence: 86%
“…Taken together, the results of cross-linking and LRET studies indicate that one of the subunit interfaces is similar to that observed in the CYP3A4 x-ray structure 1W0F, where Cys 239 residues of two subunits are located in close proximity to each other. These findings strengthen our prior inference that the peripheral steroid-binding site in the vicinity of the FЈ and GЈ helices of two interacting CYP3A4 molecules observed in the x-ray structure 1W0F is physiologically relevant (23,61). The interactions at the second type of the intersubunit interface are also likely to bring some cysteine residues other than Cys 239 of two CYP3A4 subunits into close proximity to each other.…”
Section: Discussionsupporting
confidence: 86%
“…3A4 often exhibits homo-and heterotropic activation kinetics with progesterone and other substrates of similar size that are consistent with the binding of two or more molecules to the enzyme (73,74). Biophysical studies have suggested that two molecules can stack in the active site (75), as seen for the 3A4 structure with two molecules of ketoconazole (69), and have provided evidence for a peripheral binding site such as that observed for progesterone (76).…”
Section: Drug-metabolizing Enzymesmentioning
confidence: 57%
“…However binding of the distal NNK would not be likely to alter the iron-coordinated water molecule like the more proximal molecule would. Thus spectral binding shifts may only be responsive to the NNK molecule in the active site, as has been observed for fluorol-7GA binding to CYP3A4 (44). Additionally, the proximal NNK molecule in the nonproductive orientation would be expected to yield a type II spectral shift because the pyridine nitrogen appears to coordinate to iron, but in solution only a type I spectral shift is observed, even at high concentrations, when CYP2A13 is titrated with NNK.…”
Section: Discussionmentioning
confidence: 94%